Systematic Literature Review: Penggunaan Teknologi Software Defined Networking (SDN) dalam Manajemen Trafik Jaringan Telekomunikasi - Irawan, Fajar Rayhan Putra; Veri, Jhon; Zefriyenni, Zefriyenni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to examine the application of Software Defined Networking (SDN) in telecommunication network traffic management through a Systematic Literature Review (SLR) approach. Literature data were collected from reputable databases such as IEEE Xplore, Scopus, ACM Digital Library, and ScienceDirect, then selected using PRISMA guidelines and analyzed with the assistance of Covidence and VOSviewer software. From 75 identified articles, 22 met the inclusion criteria and were analyzed in depth. The findings indicate that SDN provides high flexibility, scalability, and efficiency in network management through the separation of the control plane and data plane. SDN enables adaptive traffic engineering, automated configuration, enhanced security, and integration with Machine Learning for network optimization. Nevertheless, challenges such as the risk of a single point of failure, device interoperability, and the need for skilled human resources remain as implementation barriers. Overall, SDN has the potential to become a key technology in the transformation of modern telecommunication infrastructure to meet service demands in the digital era.